2022
DOI: 10.1111/oik.08755
|View full text |Cite
|
Sign up to set email alerts
|

Kin recognition in Drosophila: rearing environment and relatedness can modulate gut microbiota and cuticular hydrocarbon odour profiles

Abstract: From inbreeding avoidance to kin‐selected cooperation, social behaviours are frequently reliant on kin recognition. However, kin recognition mechanisms are costly to evolve and currently not very well understood. Recent evidence suggests that, by altering their host's odour, gut and other host‐associated microorganisms may provide a promising avenue for understanding kin recognition. In Drosophila melanogaster, kin recognition can mediate mate choice, sexual conflict and larval competition/cooperation, undersc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Instead, our results are consistent with the possibility that the gut microbiome may mediate familiarity/kin recognition (Lizé et al, 2013(Lizé et al, , 2014, to the extent that mating avoidance between individuals with similar microbial profiles may promote outcrossing. Interestingly, in Drosophila, the gut microbiota appears to influence kin recognition via modifications of cuticular hydrocarbons, thereby shaping the scent profiles used in mate choice (García-Roa et al, 2022;Lewis et al, 2014). Bacterial symbionts support cuticle synthesis and have the potential to interfere with the host's cuticular hydrocarbon profile in several insects, including beetles (Engl & Kaltenpoth, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, our results are consistent with the possibility that the gut microbiome may mediate familiarity/kin recognition (Lizé et al, 2013(Lizé et al, , 2014, to the extent that mating avoidance between individuals with similar microbial profiles may promote outcrossing. Interestingly, in Drosophila, the gut microbiota appears to influence kin recognition via modifications of cuticular hydrocarbons, thereby shaping the scent profiles used in mate choice (García-Roa et al, 2022;Lewis et al, 2014). Bacterial symbionts support cuticle synthesis and have the potential to interfere with the host's cuticular hydrocarbon profile in several insects, including beetles (Engl & Kaltenpoth, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lizé et al (2014) provided evidence for a role of gut bacteria in kin recognition in Drosophila. Here, the microbiome appears to affect copulation preference as a function of familiarity (D. bifasciata) and diet (D. melanogaster), potentially via changes in the composition of the hosts' cuticular hydrocarbon compounds (García-Roa et al, 2022;Lewis et al, 2014). Intriguingly, Sharon et al (2010Sharon et al ( , 2011 also showed that some components of the gut microbiome of two D. melanogaster lines reared on different food sources were responsible for assortative mating-an observation that hints at a potential role for microbial symbionts in reproductive isolation and ecological speciation.…”
Section: Introductionmentioning
confidence: 99%
“…It is already a model system in sexual conflict studies, exhibiting intense sexual conflict that includes both precopulatory (i.e., male harassment; Teseo et al, 2016) and post‐copulatory (i.e., toxic ejaculates (Wigby & Chapman, 2004, 2005)) harm to females. It is also capable of kin recognition in both its larval (Khodaei & Long, 2019) and adult stages (García‐Roa et al, 2022; Lize et al, 2013; Tan et al, 2013). Moreover, previous evidence has shown evidence of cooperation among kin (Khodaei & Long, 2019, 2020), and it is the first species in which males were shown to decrease male harm when competing against related males (Carazo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gut microbiota has been shown to play an important role in kin recognition in D. melanogaster (García-Roa et al, 2022;Heys et al, 2018;Lize et al, 2013). Gut microbiota is transferred into the medium by females during oviposition, and is heavily influenced by environmental factors, including the food regime flies are kept in (Broderick & Lemaitre, 2012;García-Roa et al, 2022). Consequently, the gut microbiome of laboratory flies kept under the same food is bound to exhibit considerably less inter-individual variation than in nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation